PERTUMBUHAN DAN PERKEMBANGAN TUNAS PADA BIBIT NYAMPLUNG HASIL PEMBIAKAN DENGAN TEKNIK SAMBUNGAN - Hamdan Adma Adinugraha; nfn Mahfudz; Ekawati Wahyuning Muchtiari; Sih Huda (Jurnal Pemuliaan Tanaman Hutan, 2012)
Callophyllum inophyllum Linn. is one of potential tree species for commercial plantation as biofuel sources. This species was generally propagated by generative method and seldom vegetative method in mass planting stock production. A completely randomized design was arranged in factorial experiment to identify the effect of three grafting methods and four origins of scion in mother tree on the growth of grafted plants. The growth of grafted plants was observed at nursery and the  development of graft union anatomy was observed through microscopic method in laboratory. The result showed that grafting method significantly influenced to shoot number and shoot length, with the best result showed by veneer graft method. Position of scion in mother trees influenced shooting rate and the best result was gained through the scion from the lower part of the tree crown. The survival rate was 72-100%, shooting rate was 68-100% with 1,9 shoots per grafted and average of shoot length was 0,65 cm.The growth of graft union showed earlier by callus formation and then differentiated to a vascular tissue